Investigation of the Influence of Price, Promotion and Innovation on Customer Satisfaction in the Digital Era - Prayuda, Rafie Zaidan (UJoST- Universal Journal of Science and Technology, 2024)
The aim of this research is to analyze the influence of price, promotion and innovation on customer satisfaction. This research is research using quantitative methods. This study used a sample size of 345. Variable measurements in this study used a Likert scale of 1 – 5, Strongly disagree = 1, disagree = 2, neutral/doubtful = 3, agree = 4 and strongly agree = 5. This study used SmartPls analysis tool to test the feasibility of data and draw conclusions in hypotheses. The outer model test and inner model test are the analytical tools that will be used in this research. The research results show that price, promotion and innovation have a positive and significant relationship with customer satisfaction. The results of this research provide important innovations in strategic management, for companies and industry. Researchers hope that this research can be useful for the wider community and the telecommunications industry. Future researchers are expected to be able to add other independent variables such as social media marketing, consumer loyalty, brand image, brand trust, service quality, motivation and many more that can explain the influence on satisfaction that was not examined in this research.